Predictors with regard to ingestion, inhalation and dermal absorption of estimated phthalate daily intakes in pregnant women: The Barwon infant study. (June 2020) - Sugeng, Eva J.; Symeonides, Christos; O'Hely, Martin; Vuillermin, Peter; Sly, Peter D.; Vijayasarathy, Soumini; Thompson, Kristie; Pezic, Angela; Mueller, Jochen F.; Ponsonby, Anne-Louise; ,
Graphical abstract: Highlights: Phthalates levels, ubiquitously distributed in maternal urine, varied 1000-fold. Multiple factors from various exposure routes were associated with phthalate levels. High-fat milk and tinned food consumption were predictors of phthalate exposure. Volatile household product use was associated with higher phthalates. Reported plastic avoidance behavior was not associated with lower phthalate levels. Abstract: Human exposure to phthalate chemicals, used in consumer product plastics, occurs throughout the day. Phthalate levels in pregnant women are associated with offspring health effects including obesity and neurodevelopmental problems. Knowledge of predictors of exposure is necessary in order to effectively reduce phthalate exposure. The present study aims to identify predictors of phthalate levels in Australian pregnant women from the Barwon Infant study birth cohort. Maternal urine samples from 841 women were analyzed for phthalate metabolites. Maternal diet and food preparation practices, use of volatile household products, household characteristics and personal care product use were assessed with questionnaires. All maternal urine contained phthalate metabolites. Maternal prenatal high-fat milk consumption was associated with higher benzyl butyl phthalate (BBzP) (p < 0.001), and bis(2-ethylhexyl) phthalate (DEHP) (p = 0.0023). Higher phthalate levels were associated with consumption of tinned food (fish and tomatoes). Diethyl phthalate (DEP) levels were significantly higher when women reported using air freshener (35% increase, p = 0.01), aerosols (40% increase, p = 0.005), hair treatment chemicals (28% increase, p = 0.031), and chlorine (34% increase, p = 0.009) compared to no use. Maternal phthalate levels did not vary by reported plastic avoidance during pregnancy. The study showed that phthalate exposure is ubiquitous and increased by multiple factors. Future intervention studies to reduce phthalate levels among pregnant women will need to take into account the variety of sources identified in this study.